Alternative Ökonomie. CD-Rom-Edition. - (:unkn) unknown (AG SPAK-Bücher, 2006)
Die digitalisierte Ausgabe enthält 19 Bücher des Verlages.
Keywords: Wirtschaftspolitik; Wirtschaft; Arbeitsmarkt; Genossenschaft; Selbstverwaltung; Alternative Ökonomie; Wirtschaftsunternehmen